An annotated checklist of scale insects (Hemiptera: Coccoidea) of Portugal, including Madeira and Azores Archipelagos - Franco, José Carlos; Russo, Agatino; Marotta, Salvatore (Zootaxa, 2011)
A first comprehensive checklist of the scale insects of Portugal, including Azores and Madeira Archipelagos, is presented comprising a total of 168 species: 124 from Mainland, 109 from Madeira, and 52 from Azores. The listed species are distributed among 85 genera and 15 families.